Legal Protection for Children and Women Victims of the Palestine Israel War from the Perspective of Islamic Humanitarian Law - Rosman, Edi; Wadi, Fajrul Wadi; Wahyuni, Zikra Wahyuni (GIC Proceeding, 2024)
The prolonged conflict between Palestine and Israel has significantly impacted children and women as vulnerable groups. This article analyzes the legal protection for them through the perspective of Islamic humanitarian law. Islamic humanitarian law, rooted in Sharia principles, emphasizes the protection of non-combatants in armed conflicts. Children and women, as parties not directly involved in warfare, are guaranteed security and special protection based on various texts from the Qur’an and Hadith. Additionally, the principles of maqasid al-shariah (objectives of Sharia), which prioritize the protection of life, lineage, and property, reinforce this protective argument. This study identifies the alignment between international humanitarian law and Islamic humanitarian law regarding the protection of vulnerable groups during conflicts. However, implementation on the ground is often hindered by political and military complexities. Therefore, intensive efforts from the international community and Muslim countries are needed to ensure adherence to the principles of Islamic humanitarian law. The article concludes that strengthening legal protection for children and women victims of the Palestine-Israel conflict requires a holistic approach that combines international norms and Islamic values to achieve better justice and humanity